INTEGRATED INVESTMENT CLIMATE AS A KEY FACTOR FOR SUSTAINABLE DEVELOPMENT OF UKRAINE’S ECONOMY - KOTSKO, Taras; ARTEMENKO, Lina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The object of the study in the article is the problems of forming an integrated investment climate of Ukraine in the context of creating prerequisites for sustainable development. Special attention is paid to the role of the integrated system of investment climate components in ensuring the institutional efficiency of the economic system, in forming stable and predictable conditions for investment activity, and in promoting the reorientation of investment flows toward the priorities of sustainable development. The components of the integrated investment climate and the features of their mutual influence are revealed and characterized. The key role of the institutional component in the integrated investment climate system is revealed. It is proven that the structural ramification of the integrated system of the investment climate and the coordinated interaction of its components are two defining features that form the potential for sustainable development. Attention is focused on the fact that despite the prolonged military and political turbulence caused by external aggression, the issue of the transition of the national economy of Ukraine to a model of sustainable development retains the status of a fundamental reference point in the system of socio-economic reforms, post-war recovery processes, and the development of a competitive economic system on a new structural basis. It has been proven that an integrated investment climate plays a decisive role in ensuring the progressive development of the economic system in the direction of sustainable development, since it acts not only as a factor in increasing investment attractiveness, but also as an important tool for strengthening the adaptability of the national economy based on the activation of a complex of mechanisms for its self-development. The need to integrate sustainability priorities into the mechanisms of economic policy for post-war economic development is substantiated as an important condition for the formation of a qualitatively new basis for progress toward sustainable development.